D’un mode d’habiter à l’autre : modalités et significations de la réappropriation d’un pavillonnaire des Castors à Oran (Algérie) - Madjid Chachour; Nadia Belas (Territoire en Mouvement)
In Algeria during the years 1953-1958, most of the achievements of the French pavilions of « Castor » housing estates are concentrated in Oran. Produced during the colonial period in self-construction and in accordance with the model implemented in France, the houses are arranged in the form of a stereotyped « Pavilion model » and are adapted to a particular category of the European population. After the departure of this population in 1962, these residential suburbs have been gradually transformed by the new Algerian occupants. Starting from this « substitution », numerous questions relate the way of their re-appropriation. The case of the subdivision of Familiaux and Traminot Castors (CFT) from Maraval (district of El-Othmania in Oran), in which we conducted a qualitative survey between 2010 and 2013, revealed to us the importance of the socio-spatial readjustments. A process of appropriation that has defined, on the one hand, the contours of the different forms of transformation that prevail in their organizations, and has brought out, on the other hand, from the remodeling of the original pavilion model, a type of hybrid habitat, using Algerian and Western cultural references. Thus, the article proposes to show the extent of the changes in the mode of dwelling in the practical and symbolic dimensions of space, through new arrangements of facilities, and to highlight in particular, the role of residential transformations in the affirmation of the social and economic status of the purchasers. Its objective is to question the future of a European suburban residential heritage dating from the middle of the 20th century, whose outlines are progressively altered.